?ADAPTABILITY OF SEMIDWARF SPRING WHEAT IN SINDH PROVINCE (Biological Sciences - PJSIR, 1999)
The improvement of yield stability in spring wheat is a major plant breeding objective. The yield of ten spring wheatgenotypes were determined for three seasons (1992-1994) at nine sites in Sindh province. The genotypes environmentsinteraction was highly significant (P~O.OI). Heterogeneity between regression for genotypes (P~O.05) and deviation fromregression (P:::;O.OI)were significant. Genotype SI88123 had the highest mean yield over environment and was generallyadapted to all the environments. WRS-OI, SI88155 and SI88231 had lower mean yield over environments.